The Effect of Yoga with Motivational Interviewing During Pregnancy on Physical Activity - Marfuah, Dewi; Fitriana, Anisa Nur; Mutiar, Astri; Juniarni, Lia (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2024)
Aims: Physical activity is crucial for a healthy pregnancy, promoting physical and mental health. Pregnant women can reduce weight gain, low back pain, and high-risk pregnancies. Yoga is a structured exercise for increased physical activity. Motivational Interviewing (MI) can encourage safe physical activity behavior in pregnant women. Knowing the effect of Yoga with Motivational Interviewing on physical activity in pregnant women. Methods: This study used a quasi-experiment design, dividing 52 pregnant women into two groups: 26 intervention and 26 control groups. The intervention involved yoga and weekly physical activity, with data collected using the PPAQ. Results: The effect of providing Structured Exercise Training and Motivational Interviewing interventions on physical activity in pregnant women Wilcoxon Test with a p-value of 0.003 (significant <0.05) and the Mann-Whitney Test p-value 0.001 (significant <0.05) which means that the hypothesis is accepted. ANCOVA results in p-value 0.000. Conclusions: Research in obstetric clinics and community settings reveals the impact of yoga and MI on pregnant women. Structured exercise training and motivational interviewing can increase physical activity in pregnant women. The study suggests improving education and facilities for yoga in obstetric clinics and communities.